Increasing Flavonoid Content of Red Beet (Beta vulgaris L.) through Providing Shade and Potassium - Pasaribu, Enita; Udayana, Cicik (Department of Agronomy, Faculty of Agriculture, Brawijaya University, 2026)
Application of potassium and intensity of sunlight might affect flavonoid content on the red beet. This research aims to determine optimal shade density and potassium dosage to enhance the flavonoid content on red beet. The research was conducted in Temas Village, Batu, East Java, at an altitude of 790 meters above sea level, with an average temperature of 22.25oC and humidity ranging from 77% to 95%. The research used a split plot design with two factors: shade percentage (25%, 50%, 75%) and potassium dosage (48 kg ha-1, 96 kg ha-1, 144 kg ha-1) by repeating three times. Result of the research showed an application of 75% shade and 96 kg ha- 1 potassium produced higher flavonoid content compared to other treatments. The highest biomass dry above the ground and fresh tuber weight were obtained with 25% of shade. Meanwhile, biomass dry above the ground and fresh tuber weight were higher with the application of 96 kg ha-1 potassium.